Kebijakan Penanggulangan Kejahatan Dengan Sarana Penal Dan Non Penal Terhadap Tindak Pidana Narkotika Anak Sebagai Pelaku - Paulus H Sinaga; Rizkan Zulyadi; M. Citra Ramadhan (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
This research focuses on the form of punishment for children who commit narcotic crimes based on Indonesian laws and regulations. obstacles to law enforcement against children as perpetrators of narcotics crimes in the Medan City Region. penal and non penal policy strategies carried out by the Indonesian National Police in tackling Narcotics Crimes by children. The research method used is normative juridical. The data was collected by means of a literature study which was sourced from secondary data consisting of primary, secondary and tertiary legal materials, then analyzed qualitatively. The results of the first research are that the form of punishment for children who commit narcotic crimes under the law can be subject to criminal sanctions in the form of imprisonment and sanctions in the form of medical and social rehabilitation. The imposition of criminal sanctions for children is used as an ultimum remedium. Obstacles to Law Enforcement Against Children as Perpetrators of Narcotics Crime in the Medan City Region can be categorized into internal constraints and external constraints. Internal obstacles consist of the presence of the police who back up/protect drug dealers so that raid information is always leaked, minimal operational funds, limited human resources in the Medan Polrestabes narcotics unit, and the lack of arresting tools in eradicating narcotics. While the external constraints consist of, the environment is not good, the rise of nightclubs, the changing modus operandi, the presence of new types of drugs. The non-penal policies carried out by law enforcement officials consist of counseling, outreach, collaboration, anti-drug campaigns, with the distribution of pamphlets and social media, as well as the establishment of the Anti-drug Tangguh Village Command Post to prevent the abuse and illicit trafficking of narcotics in Medan City. The Penal Policy is carried out by applying criminal, medical and social rehabilitation for children who are involved in narcotics crimes.